Planning Education in the Case Study of the Course of Metropolitan Planning in Istanbul - (:unkn) unknown (My University, 2018)
This paper examines the courses, which are called “Metropolitan Planning in Istanbul”in Marmara University, using a Bourdieu’s participant objectivation method.These courses are in Global Cities and Istanbul Studies Master’s Program inwhich there is a protocol between Marmara University and Turkish Association ofMunicipalities. Most of students in this program have been working at differentlevel management in several municipalities. They got a scholarship according tothe protocol. The courses are about planning theory and practices. The center ofdiscussion in these courses is the planning agenda of Istanbul. This text discussesthe possibilities and the hidden hardships of teaching planning, using the IstanbulMetropolitan Planning course in 2016-2017 academic year, as a case study.

Bu makale Marmara Üniversitesi’nde sunulan “İstanbul’da Metropoliten Planlama” başlıklı dersleri Bourdieu’nun katılımcı nesneleştirme metodunu kullanarak incelemektedir. Bu dersler, Marmara Üniversitesi ve Türkiye Belediyeler Birliği arasındaki işbirliğinin protokole bağlandığı Küresel Şehirler ve İstanbul Araştırmaları Yüksek Lisans Programı’nda yer almaktadır. Programdaki öğrencilerin çoğunluğu burslu ve çeşitli kademelerde görevli yerel yöneticilerdir. İncelenen dersler kentsel planlama teori ve pratiğini konu almaktadır, derslerdeki tartışmanın odağında İstanbul planlama gündemi bulunmaktadır. Bu yazı, planlama eğitiminde gizli kalan zorlukları ve olanakları, 2016-17 akademik yılındaki İstanbul Metropoliten Planlama dersleri örneğinde tartışmaktadır.
‘İstanbul`da Metropoliten Planlama’ Dersi Örnek Olayı Çerçevesinde Planlama Eğitimi
Keywords: İktisat; İşletme